Meta_Body: Virtual Corporeality as a Shared Creative Process - Sousa, Catarina Carneiro de (2022)
This chapter discusses the Meta_Body participatory art project. Initiated in a collaborative virtual environment and in a “real life” art exhibition, it now continues in the metaverse creative flux. Meta_Body focuses on two aspects: first, the avatar as body/language, open to experimentation and potency; second, avatar building as a shared creative process and as aesthetical experience. Through the practice of avatar creation, distribution, embodiment and transformation, the artists aim to understand the processes of virtual corporeality constitution: to question the role of the body in virtual environment, its importance in engaging with the world and in self-expression, and explore its metaphorical aspects. The method used to implement this project is a shared creative process, in which multiple subjects come to be authors along different phases of the project. Through the embodiment and transformation of avatars, the artwork's aesthetical experience becomes a creative process.